Cyber resilience in Malaysia: Strengthening the digital frontier - Mazita, Mokhtar; Nor Hasnul Azirah, Abdul Hamid (School of Electrical Engineering UiTM Kampus Terengganu, 2024)
A cyber security company reported that Malaysia experienced an average of 84 millions cyberattacks per day in fourth quarter of 2022, which doubled in 2023 and may continue to rise this year. This statistics highlights the need for a revolution in traditional cybersecurity models due to the rise of sophisticated cyber attacks. In this volatile cyberspace, existing approached, which primarily focus on traditional security-related standards of protection and prediction are considered insufficient in addressing the threats. Therefore, cyber resilience is introduced as a recommended way forward.